PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN : Training, Motivation, Performance. - Kusumaningrum, Dini (Fakultas Ekonomi Universitas Gresik, 2021)
The purpose of this study is to know and analyze the effect of training and motivation on the performance of PT. Anugrah Jaya Mandiri Sidoarjo employee.The data used is PT. Anugrah Jaya Mandiri Sidoarjo employees in outlet work area. Using the saturated sampling technique, the sample was 103 respondents. The method of data collection in this study is a questionnaire. Data in process using SPSS 20.0 for window. Data methods use explanatory and quantitative methods that are regression analysis. The result is that the training and motivation variables affect the performance of PT. Anugrah Jaya Mandiri Sidoarjo employee. Coefficient determinations (R 2 ) show that the correlation between training and motivation on employee performance is 90.3%. It means it's strongly related.